2008
DOI: 10.1002/pssb.200844135
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ and nanomechanical structures for silicon carbide MEMS and NEMS

Abstract: Silicon carbide (SiC) is recognized as the leading semiconductor for high power and high temperature electronics owing to its outstanding electrical properties combined with mature processing technologies for monolithic structures. SiC has long been known for its outstanding mechanical and chemical properties making it equally attractive for mechanical structures in micro‐ and nanoelectromechanical systems (MEMS and NEMS). Recent advancements in bulk and surface micromachining have led to the development of Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 153 publications
(196 reference statements)
0
92
0
Order By: Relevance
“…A more remarkable record is achieved in optomechanical single crystal diamond micro disk resonators operating in ambient condition 12,33 , with f c · Q m = 19 THz, while similarly f c · Q m = 9.5 THz at room temperature in polycrystalline 3C-SiC optomechanical micro-resonators has been achieved (the theoretical maximum achievable in SiC being f c · Q m = 300 THz at room temperature) 34 . It is expected that a similar race could start regarding MEMS/NEMS 35 in reconsidering conventional materials, hosting color centers as diamond, such as SiC, for applications envisaged for current diamond nanomechanical resonators.…”
Section: And Citations Therein)mentioning
confidence: 99%
“…A more remarkable record is achieved in optomechanical single crystal diamond micro disk resonators operating in ambient condition 12,33 , with f c · Q m = 19 THz, while similarly f c · Q m = 9.5 THz at room temperature in polycrystalline 3C-SiC optomechanical micro-resonators has been achieved (the theoretical maximum achievable in SiC being f c · Q m = 300 THz at room temperature) 34 . It is expected that a similar race could start regarding MEMS/NEMS 35 in reconsidering conventional materials, hosting color centers as diamond, such as SiC, for applications envisaged for current diamond nanomechanical resonators.…”
Section: And Citations Therein)mentioning
confidence: 99%
“…Although Si is presently the most used material for MEMS fabrication it has serious limitations for some applications, such as high temperature (T > 300 °C) and/or harsh environments with corrosive chemicals and biocompatibility, and SiC could be a viable alternative material. Micro cantilever of 3C-SiC with oscillating frequency in the order of 10 6 Hz and Q factors of 10 3 were realized and the resonators were used for high sensing applications such as mass detection for gas sensing devices in harsh environments (Zorman & Parro, 2008). Combining MEMS and nanostructures peculiar characteristics such as high affinity to selected species via functionalization and high measurement sensitivity thanks to high resonant frequency and Q factors could open interesting possibility in detection devices for biological applications.…”
Section: Applicationsmentioning
confidence: 99%
“…A comprehensive review on the fabrication of SiC micro/nano structures can be found elsewhere. [17] A common method to remove the Si substrate is the use of Si wet-etching employing different etchants such as KOH, TMAH, or HNA. [18][19][20][21] In many cases, Si wet-etching is more preferable than dry-etching owing to its low cost, simple equipment, high etch-rate, excellent material selectivity, as well as the capability of processing multiple wafers simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] In many cases, Si wet-etching is more preferable than dry-etching owing to its low cost, simple equipment, high etch-rate, excellent material selectivity, as well as the capability of processing multiple wafers simultaneously. [22] However, since the Si-etchants are relatively aggressive, the metallization to form electrodes for SiC devices is a challenging issue. [23,24] To date, most of the suspended SiC devices fabricated using Si-wet etching rely on external sensing source, such as Raman spectroscopy and optical interferometer, while self-sensing devices utilizing electrical measurement have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%